Positive and Negative Affect Change among People Living with HIV: a One-Year Prospective Study - Rzeszutek, Marcin (Int J Behav Med, 2018)
PURPOSE: The aim of this study was to investigate the heterogeneity of changes in affective states, i.e., positive (PA) and negative (NA) affect, as well as the sociodemographic and clinical covariates of these changes among people living with HIV (PLWH) in a 1-year prospective study. METHOD: Participants were 141 ambulatory patients (15% female) with a confirmed diagnosis of HIV infection who were undergoing antiretroviral treatment. Their affective states were assessed three times, with 6-month intervals, using the positive and negative general affect scale (PANAS-X). Sociodemographic (gender, age, relationship status, education, employment) and clinical variables (CD4 count assessed via self-report, HIV/AIDS status, time since HIV diagnosis and antiretroviral treatment duration) were also obtained. RESULTS: Heterogeneity of changes was present only for NA, whereas PA decreased gradually in the whole sample. Time since diagnosis was unrelated to baseline affect levels as well as affect level changes. Additionally, the trajectories of NA and PA were independent of each other. The significant correlates of trajectories were gender and CD4 counts, both baseline CD4 levels and CD4 changes. CONCLUSION: This study adds to the literature by describing affect changes among PLWH and identifying potential correlates of these changes, particularly CD4 count and gender. As such, these findings point to the potential clinical significance of further research on the roles of these variables.